Carotenoid Profiles and Preliminary Investigation on Carotenoid Biosynthesis in the Oil Palm (Elaeis Guineensis) Mesocarp - Jane, Sonai Kaur (2002)
The oil palm fruit is one of the richest sources of carotenoids. However, little is known about the pathway for carotenoid synthesis in the oil palm. Therefore, the aim of this study is to provide some basic information on carotenoid synthesis in the oil palm mesocarp. In order to do so, we needed to firstly extract carotenoids from the oil palm mesocarp. A technique for extracting carotenoids from the oil palm meso carp was optimised. Cold saponification was used to remove unwanted lipid materials from the crude carotenoid extract. Ultra violet-Visible (UV -Vis) spectrophotometry was utilized to compare the absorbance profiles of the carotenoid extracts of oil palm fruits at different stages of development i.e 15-20 weeks after anthesis (W AA). The results showed that in unripe oil palm fruit, carotenoids absorb strongly in the UV range while in ripe fruit the carotenoids absorb strongly in the visible range as more carotenoids are formed. Reverse phase high pressure liquid chromatography (RP-HPLC) coupled with a photo-diode array (PDA) detector was used in this study for characterizing the carotenoid profiles of